The blood-brain barrier in multiple sclerosis: a target for treatment? - Vries, Elga de (Henry Stewart Talks, 2018)
Brain endothelium and the neurovascular unit, Multiple sclerosis (MS) disease course and pathology, Blood brain barrier (BBB) breakdown, Mechanisms of BBB failure in MS, Gliosis and neurodegeneration, Irreversible tissue damage through infiltration of immune cells, Targets for MS drugs, Treatments and their impact on BBB dysfunction, Restoring CNS homeostasis